Nurse-physician co-leadership: exploring a strategy to enhance quality and patient safety in U.S. Hospitals - Senn, Laura Anne (My University, 2014)
Background: The healthcare industry has been mandated by regulatory bodies to improve quality and patient safety in hospitals. The struggle to implement and sustain effective performance improvement processes is linked to leadership, especially at the department level where the rubber hits the road. Although many advances have been made, there is a sustained need to continue looking for additional strategies. A new leadership model in healthcare, nurse and physician co-leadership, may be an effective strategy to use to bridge diffuse power structures found in the knowledge-based, pluralistic organization. Effectively used by at least 10% of business worldwide, only a few hospitals across the country have implemented this leadership model. Anecdotal evidence is promising, but empirical evidence is lacking. Study Question and Aims: The research question was, "How do nurse and physician co-leaders' description of their work together reflect their roles and relationships?" The specific aims were to explore: (a) the factors that hindered or enhanced the role development of the partners; and (b) the nature and dynamics of the co-leaders' working relationship. Design: Qualitative inquiry was used to obtain evidence from practice. Eight nurse and physician co-leaders were interviewed individually about their shared role and responsibilities, and their collaborative work together within a co-leadership structure. A deductive content analysis approach was used. Coding started with nine categories, which were derived from an extensive review of the literature on co-leadership in business, education, and healthcare. Cross case analysis revealed 40+ sub-categories.Findings: Nurse-physician co-leadership is a form of plural leadership where two formal leaders together lead a hospital unit, sharing power to build a more democratic process, but also taking back power and influence from diffuse sources of power commonly found in the hospital setting. Two essential themes, the Shared Role Space: Moving from I to We and Partnered Leadership: Dynamic Interplay of Complementary Competencies, emerged from the data to describe the experience, and a conceptual framework was proposed. Numerous factors were revealed that enhanced or hindered the co-leaders' role development. The dynamic interplay of co-leaders' work together was portrayed. Conclusion: Co-leadership is different than inter-professional collaboration or teamwork. Clinicians and administrators are offered a toolkit to help ensure successful development of the nurse-physician co-leadership model in hospitals. Researchers are offered a framework to measure outcomes, but are warned about confusing terms, and the presence of intermediate outcomes in research focused on post-heroic leadership models. This plural leadership model is a strategy worth exploring to address the challenges of successfully implementing quality and patient safety innovations in hospitals.
University of Minnesota Ph.D. dissertation. May 2014. Major: Nursing. Advisor: Laura Duckett. 1 computer file (PDF); x, 141 pages, appendices A-D.
Keywords: Co-leadership; Nurse and physician leaders; Patient safety; Plural leadership; Qualitative content analysis; Quality and patient safety